Mortality in pediatric oncology and stem cell transplant patients with bloodstream infections - Willis, Daniel N.; McGlynn, Mary Claire; Reich, Patrick J.; Hayashi, Robert J. (Frontiers in Oncology, 2023)
Background Bloodstream infections (BSI) continue to represent a significant source of morbidity for pediatric oncology patients, however less is known regarding this population’s risk of death. We sought to evaluate the risk of BSI and death at a large pediatric cancer center. Methods We retrospectively collected inpatient data from pediatric oncology and hematopoietic stem cell transplant (HSCT) patients over a 9-year period. We performed univariate and multivariable modeling to assess risk of BSI and mortality examining the following variables: demographics, underlying malignancy, history of HSCT, central line type, and febrile neutropenia (FN). Results During the study period, 6763 admissions from 952 patients met inclusion criteria. BSI occurred in 367 admissions (5.4%) from 231 unique individuals. Risk factors for BSI include younger age, diagnoses of hemophagocytic lymphohistiocytosis or acute myeloid leukemia, ethnicity, and history of HSCT. Mortality for those with BSI was 6.5%, compared to 0.7% without (OR 7.2, CI 4.1 – 12.7, p<0.0001). In patients with BSI, admissions with FN were associated with reduced mortality compared to admissions without FN (OR 0.21, CI 0.05 – 0.94, p=0.04). In both univariate and multivariable analysis, no other risk factor was significantly associated with mortality in patients with BSI. Conclusion BSI is a significant source of mortality in pediatric oncology and HSCT patients. While demographic variables contribute to the risk of BSI, they did not influence mortality. These findings highlight the importance of BSI prevention to reduce the risk of death in pediatric oncology patients. Future studies should focus on comprehensive BSI prevention.